An experimental test of stabilizing forces in the field niche. Issue 4 (1st March 2021) - Siefert, Andrew; Friesen, Maren L.; Zillig, Kenneth W.; Aguilar, Jessica; Strauss, Sharon Y.
Abstract: Modern coexistence theory holds that stabilizing mechanisms, whereby species limit the growth of conspecifics more than that of other species, are necessary for species to coexist. Here, we used experimental and observational approaches to assess stabilizing forces in eight locally co‐occurring, annual, legume species in the genus Trifolium . We experimentally measured self‐limitation in the field by transplanting Trifolium species into each other's field niches while varying competition and related these patterns to the field coexistence dynamics of natural Trifolium populations. We found that Trifolium species differed in their responses to local environmental gradients and performed best in their home environments, consistent with habitat specialization and presenting a possible barrier to coexistence at fine scales. We found significant self‐limitation for 5 of 42 pairwise species combinations measured experimentally with competitors absent, indicating stabilization through plant–soil feedbacks and other indirect interactions, whereas self‐limitation was largely absent when neighbors were present, indicating destabilizing effects of direct plant–plant interactions. The degree of self‐limitation measured in our field experiment explained year‐to‐year dynamics of coexistence by Trifolium species in natural communities. By assessing stabilizing forces and environmental responses in the full n ‐dimensional field niche, this study sheds light on the roles of habitat specialization, plant–soil feedbacks, and plant interactions in determining species coexistence at local scales.